1988
DOI: 10.3168/jds.s0022-0302(88)79894-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Addition of Yeast Culture Supplement to Diets of Lactating Cows on Ruminal Fermentation and Microbial Populations

Abstract: Six ruminally fistulated Holstein cows were utilized in a randomized block design to examine effects of yeast culture supplement on ruminal metabolism and apparent digestibility. Cows were fed a diet of 40% corn silage and 60% concentrate (DM basis). Treatments were control (supplement without yeast cells) and yeast culture supplement. Treatment periods were 6 wk. Ruminal pH, ammonia, molar proportions of acetate and isovalerate, and acetate: propionate ratio were lower and molar proportions of propionate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
129
4
24

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(194 citation statements)
references
References 16 publications
25
129
4
24
Order By: Relevance
“…The advantageous effect of yeast preparation on milk production, which was marked during all periods of the experiment, could also be a result of a better established fermentation pattern in the rumen compared with that in control animals (Harrison et al, 1988;Adams et al, 1995). This conclusion is supported by the higher persistence of milk yield after peak of lactation in our experiment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The advantageous effect of yeast preparation on milk production, which was marked during all periods of the experiment, could also be a result of a better established fermentation pattern in the rumen compared with that in control animals (Harrison et al, 1988;Adams et al, 1995). This conclusion is supported by the higher persistence of milk yield after peak of lactation in our experiment.…”
Section: Discussionsupporting
confidence: 79%
“…The increased fat content in milk in the group receiving the Yea-Sacc supplement could result from a change in the rumen fermentation pattern that increased acetic acid production (Harrison et al, 1988). In our earlier studies on digestion in the rumen (Strzetelski et al, 1995b), a high ratio of C 2 :C 3 (4.4) was found in bulls fed diets supplemented with Yea-Sacc.…”
Section: Discussionmentioning
confidence: 99%
“…The diet used in our study was a high-concentrate diet for the finishing of cattle. According to Harrison et al (1988) rumen fermentation is more stable in animals fed yeast culture than in unsupplemented animals. Several studies have suggested that yeast culture supplemented from the same source (Diamond V) affected the ruminal pH by increasing lactate utilisation by ruminal bacteria, which would result in the elimination of a lactate peak and the reduction of lactic acid concentrations in the rumen liquor (Piva et al, 1993;Lynch & Martin, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Feeding high-grain diets to ruminants to increase energy density has resulted in negative associative effects on fibre digestion in the rumen. Harrison et al (1988) concluded that rumen fermentation was more stable in dairy cows fed high concentrate diets supplemented with yeast culture than without the supplement, and several studies reported improved performance of dairy and beef cattle fed high-concentrate diets supplemented with yeast cultures (Higginbotham et al, 1994;Mir & Mir, 1994;Olson et al, 1994). Furthermore, inclusion of yeast culture in the diets of dairy cows produced variable responses in tolerance to heat stress (Higginbotham et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Differing effects were obtained by Arcos-Garcia et al (1999) who observed changes in dry matter degradation affected by the addition of live yeast cultures only after 48 h incubation (Levucell). The addition of yeast may increase the counts of cellulolytic bacteria (Harrison et al, 1988), and, as a consequence, improve fibre digestibility (Carro et al, 1992). In vitro experiments reported that yeast metabolites (Diamond V XP) favourably altered rumen fermentation and stimulated lactate uptake and cellulose digestion by providing growth factors such as malate to bacteria utilizing lactate, and by elevating rumen pH (Callaway and Martin, 1997).…”
Section: Discussionmentioning
confidence: 99%